PERAN PUJANGGA BARU DALAM PEMBENTUKAN SASTRA MODERN INDONESIA ANTARA TIMUR DAN BARAT (1933–1942) - Darin Naila Mukaromah; Sayidatul Lifia Nur Fatikhatuz Zahro; Siti Nurfatma Wati; Moh Fikri Zulfikar (Universitas Nias Raya, 2026)
This study aims to examine the role of the Pujangga Baru movement in shaping modern Indonesian literature during the period 1933–1942, focusing on the dialectical tension between Eastern values and Western influences. This research employs a qualitative method with a library research approach through the analysis of various literary sources related to the development of modern Indonesian literature. The results show that the Pujangga Baru era was marked by the emergence of the Poedjangga Baroe magazine as a medium for writers to express their literary ideas and creativity within the framework of national identity formation. During this period, Indonesian literature underwent significant development in terms of modern Indonesian language use, cultural themes, nationalism, and social reflection. The influence of Western modernism and Eastern spiritual values dialectically shaped the intellectual orientation and literary works of writers during that era, as reflected in the 1935 Cultural Polemic. In conclusion, the Pujangga Baru period played a strategic role in the development of modern Indonesian literature, particularly in shaping cultural identity, strengthening the position of the Indonesian language, and producing more modern and intellectual literary works.